2012
DOI: 10.2478/10004-1254-63-2012-2164
|View full text |Cite
|
Sign up to set email alerts
|

Ageing, Arterial Blood Pressure, Body Mass Index, and Diet

Abstract: For three decades we followed up for longevity indicators, including diet, arterial blood pressure, and body mass index 379 mobile, long-living persons from Croatia, now aged 70 to 92 years, of whom 167 men aged (78.6±4.0) years and 212 women aged (77.9±4.1) years. One hundred and ninety-fi ve were from the continental and 184 from the coastal Croatia. The participants were examined in 1972, 1982, and again in 2006/7. Changes in body mass index (BMI), arterial blood pressure (ABP), and in answers to our Food F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
2
1
0
Order By: Relevance
“…Hypertension is common in elderly people, and undiagnosed hypertension increases with age. In line with earlier research, our data showed that the risk of undetected hypertension was high among older person ( 33 35 ). Overall prevalence of undiagnosed hypertension among men and women was similar.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Hypertension is common in elderly people, and undiagnosed hypertension increases with age. In line with earlier research, our data showed that the risk of undetected hypertension was high among older person ( 33 35 ). Overall prevalence of undiagnosed hypertension among men and women was similar.…”
Section: Discussionsupporting
confidence: 93%
“…But men over the age of 50 were more likely than women of the same age to have undiagnosed hypertension, which may indicate that older men had lower levels of awareness, and/or participation in early detection initiatives. This is in line with the findings of a study that found older males were less likely to be aware of their hypertension diagnosis, receive treatment for it, or have it under control than women of the same age ( 35 ).…”
Section: Discussionsupporting
confidence: 90%
“…BMI was also observed to be independently associated with age among males in northeast India by Mungreiphy, Kapoor, and Sinha (2011 was statistically significant between all age groups except for 40-49 yr and 50-59 yr age groups (Mungreiphy et al, 2011). Studies by Pavlovic, Milkovic-Kraus, Jovanovic, and Hercigonja-Szekeres (2012) and Guo, Zeller, Chumlea, and Siervogel (1999) also support age related decreases in BMI.…”
Section: Discussionmentioning
confidence: 77%